Regulatory pathway for generic and new drug registration in China and Russia - Sandeep, Dr. D. S. (Asian Journal of Pharmaceutics (AJP), 2023)
Objectives: The objective of present work is to understand the regulatory requirements and registration process of generic and new drugs in China and Russia. Methods: The dossier for the generic and new drugs should be submitted in electronic common technical document (eCTD) format to both the countries China and Russia, since both countries follow the same format of eCTD. All the modules of CTD are almost same for both the countries except module 1. Module 1 differs from country to country. Results: In China, drug marketing authorization applications, drug clinical trial application drug registration applications and supplemental applications which are required for manufactured products that are reviewed by the Drug Evaluation Center of National medical products administration (NMPA). In Russia, the National Centre of Pharmaceutical products (FGU) oversee the quality, effectiveness, and protection of all the generic and new drug products. Conclusion: From the current study, it was concluded the regulatory authorities of both China and Russia have almost the similar regulatory documents and requirements for the approval of generic and new drugs. The major difference is found in the language submission of dossiers. Roszdravnadzor allows Russian language while NMPA allows submission by using standard Chinese language in China. The safety, efficacy, quality of the drug products is the main objective of both authorities.